An efficient multi-enzyme cascade platform based on mesoporous metal-organic frameworks for the detection of organophosphorus and glucose. (1st July 2022) - Cao, Xiyue; Guo, Yanmei; Zhao, Mu; Li, Jie; Wang, Chonglin; Xia, Jianfei; Zou, Tingting; Wang, Zonghua
Highlights: An efficient and sensitive detection platform based on multi-enzyme cascade method has been developed. The platform encapsulate AChE, HRP and CHO in CF-ZIF-8 through one-step co-precipitation method. CF-ZIF-8 provides a good microenvironment for guaranteeing the activity and spatial proximity of encapsulated enzymes. The platform has high sensitivity, specificity and simplicity for acephate detection. Abstract: An efficient colorimetric detection platform based on multi-enzyme cascade has been developed for detection of organophosphorus. Firstly, the dual-enzyme platform was prepared and applied for sensitive glucose detection (detection limit 0.32 μM). And then three enzymes, including acetylcholinesterase, horseradish peroxidase and choline oxidase were encapsulated in cruciate flower-like zeolitic imidazolate framework-8 (CF-ZIF-8) through one-step co-precipitation to construct detection platform with acetylcholine chloride as substrate. The acephate inhibited the activity of acetylcholinesterase, obstructed the cascade reaction and reduced the production of H2 O2, resulting in the changes of color intensity for the colorimetric detection. With suitable size and porous structure, CF-ZIF-8 provided a good microenvironment for guaranteeing the activity and spatial proximity of enzymes. The multi-enzyme platform displayed great performances with the detection limit of 0.23 nM for acephate. It was applied to the detection of acephate in Chinese cabbage and romaine, verifying the practicability of this platform.